Natural history of Peucetia flava (Araneae, Oxyopidae): seasonal density fluctuation, phenology and sex ratio on the glandular plant Rhyncanthera dichotoma (Melastomataceae) - Morais-Filho, Jose Cesar [UNESP]; Romero, Gustavo Q. [UNESP] (Taylor & Francis Ltd, 2009)
The seasonal density fluctuation, phenology and sex ratio of Peucetia flava (Oxyopidae) on Rhyncanthera dichotoma (Melastomataceae) were investigated during a year in a swamp in southeastern Brazil. Peucetia flava displayed an unusual non-seasonal life cycle and the population size varied little over the year. The density of Peucetia spiders increased with the increase in abundance of leaves and number of arthropods adhered to glandular trichomes on R. dichotoma leaves. Our findings suggest that seasonal density fluctuation of Peucetia may be influenced by foraging site availability (i.e. leaves) and prey supply (i.e. arthropods adhering to glandular trichomes). The unusual seasonal stability of P. flava may be related to the type of habitat in which this spider occurs (swamp), because of the constant input of allochthonous resources from the water source, i.e. aquatic insects that migrate to the terrestrial environment.
Keywords: Peucetia; Animal-plant interactions; seasonal fluctuation; swamp; Neotropical